Kasus dan Penanganan Luka Bakar Derajat 1 dan Derajat 2 pada Pasien Anak-anak - Azizza, Zahra Qori; Angraini, Dwi Indria; Berawi, Khairun Nisa (CV. Jasa Sukses Abadi, 2024)
Combustio are injuries that occur on the surface of the skin due to fire or objects with high temperatures and cause damage to the epidermis and surrounding tissue. Many combustio occur due to unplanned events so children often become victims. The high incidence of combustio in children is caused by children's impulsiveness, lack of children's awareness, high activity levels, and low control by parents. Children often suffer 1st degree combustio which is erythema of the skin and 2nd degree combustio which is damage of epidermis to the reticular layer. Treatment of 1st and 2nd degree combustio in children generally uses dressings combined with hyaluronic acid to speed up the healing process. This article is a literature review and used reference articles that published in 2012-2022 on Google Scholar, Science Direct, and PubMed.